The Effect of Thermal Stratification on Unsteady Parabolic Flow past an Infinite Vertical Plate with Chemical Reaction - Nath, Rupam Shankar; Deka, Rudra Kanta; Kumar, Himangshu (East European Journal of Physics, 2023)
This research paper investigates the effects of thermal stratification on unsteady parabolic flow past an infinite vertical plate with chemical reaction. Using the Laplace transform method, analytical solutions are derived to simulate the physical process of the flow. The study considers the effects of thermal stratification on the flow field, as well as the effects of chemical reaction on the velocity, and temperature field. The results of the stratification case are then compared to the case of no stratification of a similar flow field. The results of this research can be used to improve understanding of the unsteady parabolic flow in thermal stratified environments and provide valuable insight into the effects of chemical reactions on the temperature field.